Pembelajaran pecahan menggunakan puzzle pecahan kelas 3 SD di MI Al Huda Tumpang Blitar - Sari, Intan Permata (Maliki Interdisciplinary Journal, 2024)
Mathematical education that is perceived as informal can be learned easily by using a variety of media in the learning process and requires appropriate visual comprehension. One learning resource that can be utilized is the puzzle game. Through puzzles, we can make learning more engaging for students and make learning easier for them to understand. Pecahan media puzzles are regarded as educational tools that can assist students in understanding pecahan concepts in a clear and entertaining way. The research used a quasi-experimental design with a pretest-posttest design. Subject of the study involves third-grade students at an ibtidaiyah madrasah. The students are divided into many groups: each group will conduct an experiment using a puzzle-type media. Data is collected through pre-intervention and post-intervention skills as well as observations during the ongoing learning process. Students that use the puzzle pecahan media to learn are more enthusiastic. Data was collected through fraction ability tests before and after intervention as well as observations during the learning process. Students who learn using fraction puzzle media show higher enthusiasm and are able to solve fraction problems better compared to teaching fraction material before using fraction puzzle media. Apart from that, observations also show that fraction puzzle media can increase interaction between students and teachers, as well as between students in group learning activities. The practical implication of this research is that interactive and game-based learning media can increase students’ learning motivation and facilitate understanding of abstract concepts in mathematics. It is hoped that by using this media, the fraction material presented can be more easily understood by elementary school students in particular and make it easier for teachers who teach in general.